Development and initial application of a blade design methodology for overspeed power-regulated tidal turbines. (September 2016) - Gracie-Orr, Katie; Nevalainen, Thomas M.; Johnstone, Cameron M.; Murray, Robynne E.; Doman, Darrel A.; Pegg, Michael J.
Highlights: Metrics measuring impact of blade design changes for overspeed power regulation. Use of these metrics in a one-at-a-time sensitivity and design space analysis. Cavitation inception analysis and plots within the design methodology. Consideration of alpha and dQ across blade at key operating points. Combinations of blade design changes improving performance. Abstract: The range and variability of flow velocities in which horizontal axis tidal stream turbines operate introduces the requirement for a power regulation method in the system. Overspeed power regulation (OSPR) has the potential to improve the structural robustness and decrease the complexity associated with active pitch power regulation methods, while removing the difficulties of operating in stalled flow. This paper presents the development of a methodology for the design of blades to be used in such systems. The method requires a site depth, maximum flow velocity and rated power or flow speed as input parameters. The pitch setting, twist and chord distribution were set as input parameters, variable through the use of alteration functions. Rotor performance has been broken down into OSPR performance metrics which consider coefficients of power and thrust, and cavitation inception. Three visual-numerical tools have been developed: the OSPR performance metrics were used in conjunction with a one-at-a-time sensitivity analysis approach to develop a design space; cavitation inception analyses gave plots of converging cavitation and pressure terms for each blade section; the local angle of attack and torque distribution across the blade designs were plotted at key turbine operation states. Alterations to pitch setting and twist distribution are shown to have most impact upon the design requirement of increased gradient in the rotor speed-efficiency relationship in the overspeed region; coupled with such alterations, targeted changes to the chord distribution have been shown to increase the maximum efficiency. The prevention of cavitation has been highlighted as a driver for speed-limiting design alterations. While facilitating blade design, the methodology also produces experiential knowledge which can be stored, and shared in graphical format.